Productivity and profitabilityof mustard (Brassica juncea L.) as influenced by plant growth regulators and irrigation levels - AbhinavYadav; HV Singh; RS Jat; RL Choudhary; ML Dotaniya; VD Meena; MK Meena; VV Singh (Journal of Oilseed Brassica, 2025)
The field study was carried out during rabi 2020-21 to assess the effect of plant growth regulators and irrigation levels on seed yield and economic feasibility of Indian mustard. There were three irrigation levels in main plots viz., no irrigation, one irrigation at 40 days after sowing (DAS) and two irrigations (at 40 and 75 DAS) with six treatments viz., control, naphthalene acetic acid (NAA) @ 100 ppm, gibberellic acid @ 50 ppm, salicylic acid @ 100 ppm, thiourea @ 0.1% and indole acetic acid @ 50 ppm at 30 and 60 DAS were allotted to sub-plots. Results revealed that maximum growth, number of branches/plant and plant dry weights were found under the application of two irrigations with salicylic acid. Further, yield and its attributes such as number of siliquae/plant, siliquae length, number of seeds/siliquae, seed and stover yield were recorded higher in salicylic acid with two irrigations. The maximum B-C ratio (2.47) was calculated in two irrigations with application of salicylic acid (2.36). Thus, it can be concluded that application of two irrigations with the use of salicylic acid could be beneficial for getting higher yield of Indian mustard under semi-arid region of Rajasthan